Innovation in Modeling and Simulation of Active Vibration Control for a Photovoltaic Structure Simulation - ouni, Nizar el; Boukhriss, Mokhless; chaari, riadh; Haddar, Mohamed (Journal of Vibration Testing and System Dynamics, 2026)
Photovoltaic (PV) structures are increasingly deployed in environments where they are exposed to dynamic loads, particularly wind-induced vibrations. These vibrations can negatively affect the mechanical stability, performance, and energy efficiency of the system. This paper presents a numerical study focused on the implementation of active vibration control (AVC) using piezoelectric materials integrated into PV structures as both sensors and actuators. A simplified lumped-parameter dynamic model is developed to simulate the structural response of PV panels subjected to variable wind loads. The control strategy is based on a Linear Quadratic Regulator (LQR), which is designed to minimize displacement and improve system stability in real time. MATLAB simulations are conducted to investigate the influence of several parameters, including structural stiffness, panel inclination angle, thickness, and aerodynamic load. The results show a significant reduction in vibration amplitudes when active control is applied, even in the presence of sinusoidal disturbances. This work provides a foundational framework for integrating smart materials and adaptive control algorithms into future PV panel designs, improving their durability and efficiency under fluctuating environmental conditions.